Association Between Postoperative Long-Term Heart Rate Variability and Postoperative Delirium in Elderly Patients Undergoing Orthopedic Surgery: A Prospective Cohort Study - Sun, Jiaduo; Zhang, Qingguo; Lin, Baojia; He, Mengjiao; Pang, Yimin; Liang, Qibo; Huang, Zhibin; Xu, Ping; Que, Dongdong; Xu, Shiyuan (Frontiers in Aging Neuroscience, 2021)
Background: Postoperative delirium (POD) is a common complication after orthopedic surgery in elderly patients. The elderly may experience drastic changes in autonomic nervous system (ANS) activity and circadian rhythm disorders after surgery. Therefore, we intend to explore the relationship between postoperative long-term heart rate variability (HRV), as a measure of ANS activity and circadian rhythm, and occurrence of POD in elderly patients. Methods: The study population of this cohort was elderly patients over 60 years of age who scheduled for orthopedic surgery under spinal anesthesia. Patients were screened for inclusion and exclusion criteria before surgery. Then, participants were invited to wear a holter monitor on the first postoperative day to collect 24-h electrocardiographic (ECG) data. Parameters in time domain [the standard deviation of the NN intervals (SDNN), mean of the standard deviations of all the NN intervals for each 5-min segment of a 24-h HRV recording (SDNNI), and the root mean square of successive differences of the NN intervals (RMSSD)] and frequency domain [heart rate (HR), high frequency (HF), low frequency (LF), very low frequency (VLF), ultra low frequency (ULF), and total power (TP)] were calculated. Assessment of delirium were performed daily up to the seventh postoperative day using the Chinese version of the 3-Minute Diagnostic Interview for CAM-defined Delirium (3D-CAM). The relationship between HRV and POD, as well as the association between HRV and duration of POD, were assessed. Results: Of the 294 cases that finally completed the follow-up, 60 cases developed POD. Among the HRV parameters, SDNNI, VLF, ULF were related to the occurrence of POD.After adjustment for potential confounders, the correlation between HRV indices and POD disappeared.Through stratified analysis, two significant negative correlations emerged: ULF in young-old participants and SDNNI, VLF, ULF in male patients. Conclusion: The lower HRV parameters may be related to the occurrence of POD, and this correlation is more significant in young-old and male patients. ANS disorders and rhythm abnormalities reflected by HRV changes may represent a possible mechanism that promotes POD.